Monetary Policy, Funding Cost and Banks' Risk-Taking: Evidence from the United States - Constantin Bürgi; Bo Jiang (Center for Economic Studies and ifo Institute (CESifo), 2022)
How much deposits and equity a bank has influences how a banks' lending responds to monetary policy. While the responsiveness for the bank lending channel has been well established, this is not the case for the risk-taking channel (RTC). We show in a value-at-risk RTC model that the lending for banks with relatively more equity and non-interest-bearing deposits should respond less to monetary policy tightening. This suggests that non-interest-bearing deposits act as "pseudo capital". In a panel of US banks, we find strong evidence in support of our model for various risk measures.
Keywords: E43; E52; G21; 330; bank lending; deposits; value-at-risk; pseudo capital